Harmful Effect of Rheinheimera sp. EpRS3 (Gammaproteobacteria) Against the Protist Euplotes aediculatus (Ciliophora, Spirotrichea): Insights Into the Ecological Role of Antimicrobial Compounds From Environmental Bacterial Strains - Chiellini, Carolina; Pasqualetti, Chiara; Lanzoni, Olivia; Fagorzi, Camilla; Bazzocchi, Chiara; Fani, Renato; Petroni, Giulio; Modeo, Letizia (Frontiers in Microbiology, 2019)
Rheinheimera sp. strain EpRS3, isolated from the rhizosphere of Echinacea purpurea, is already known for its ability to produce antibacterial compounds. By use of culture experiments, we verified and demonstrated its harmful effect against the ciliated protist Euplotes aediculatus (strain EASCc1), which by FISH experiments resulted to harbor in its cytoplasm the obligate bacterial endosymbiont Polynucleobacter necessarius (Betaproteobacteria) and the secondary endosymbiont “Candidatus Nebulobacter yamunensis” (Gammaproteobacteria). In culture experiments, the number of ciliates treated both with liquid broth bacteria-free (Supernatant treatment) and bacteria plus medium (Tq treatment), decreases with respect to control cells, with complete disappearance of ciliates within 6 hours after Tq treatment. Results suggest that Rheinheimera sp. EpRS3 produces and releases in liquid culture one or more bioactive molecules affecting E. aediculatus survival. TEM analysis of control (not treated) ciliates allowed to morphologically characterize both kind of E. aediculatus endosymbionts. In treated ciliates, collected soon after the arising of cell suffering leading to death, TEM observations revealed some ultrastructural damages, indicating that P. necessarius endosymbionts went into degradation and vacuolization after both Supernatant and Tq treatments. Additionally, TEM investigation showed that when the ciliate culture was inoculated with Tq treatment, both a notable decrease of P. necessarius number and an increase of damaged and degraded mitochondria occur. FISH experiments performed on treated ciliates confirmed TEM results and, by means of the specific probe herein designed, disclosed the presence of Rheinheimera sp. EpRS3 both inside phagosomes and free in cytoplasm in ciliates after Tq treatment. This finding suggests a putative ability of Rheinheimera sp. EpRS3 to reintroduce itself in the environment avoiding ciliate digestion.